Impaired Vigilant Attention Partly Accounts for Inhibition Control Deficits After Total Sleep Deprivation and Partial Sleep Restriction - Mao T (Dove Medical Press, 2021)
Tianxin Mao,1,2 David Dinges,3 Yao Deng,1,2 Ke Zhao,2 Zijing Yang,2,4 Hui Lei,2 Zhuo Fang,2 Fan Nils Yang,2 Olga Galli,3 Namni Goel,5 Mathias Basner,3 Hengyi Rao1– 3 1Key Laboratory of Applied Brain and Cognitive Sciences, School of Business and Management, Shanghai International Studies University, Shanghai, People’s Republic of China; 2Center for Functional Neuroimaging, Department of Neurology, University of Pennsylvania, Philadelphia, PA, USA; 3Division of Sleep and Chronobiology, Department of Psychiatry, University of Pennsylvania, Philadelphia, PA, USA; 4School of Medicine, Shanghai Jiaotong University, Shanghai, People’s Republic of China; 5Biological Rhythms Research Laboratory, Department of Psychiatry and Behavioral Sciences, Rush University Medical Center, Chicago, IL, USACorrespondence: Hengyi RaoCenter for Functional Neuroimaging & Department of Neurology, University of Pennsylvania Perelman School of Medicine, Room D502, Richards Medical Research Building, 3700 Hamilton Walk, Philadelphia, PA, 19104-4202, USATel +1 215-746-2470Email hengyi@pennmedicine.upenn.eduPurpose: Sleep loss impairs a range of neurobehavioral functions, particularly vigilant attention and arousal. However, the detrimental effects of sleep deprivation on inhibition control and its relationship to vigilant attention impairments remain unclear. This study examined the extent to which vigilant attention deficits contribute to inhibition control performance after one night of total sleep deprivation (TSD) and two nights of partial sleep restriction (PSR).Participants and Methods: We analyzed data from N = 49 participants in a one-night of TSD experiment, N=16 participants in a control experiment without sleep loss, and N = 16 participants in a two-nights of PSR experiment (time in bed, TIB = 6 h for each night). Throughout waking periods in each condition, participants completed the psychomotor vigilance test (PVT), which measures vigilant attention, and the Go/No-Go task, which measures inhibition control.Results: After TSD and PSR, participants displayed significantly slower reaction times (RT) and more lapses in PVT performance, as well as slower Go RT and more errors of omission during the Go/No-Go task. PVT deficits accounted for 18.0% of the change in Go RT and 12.4% of the change in errors of omission in the TSD study, and 23.7% of the change in Go RT and 20.3% of the change in errors of omission in the PSR study.Conclusion: Both TSD and PSR impaired inhibition control during the Go/No-Go task, which can be partly accounted for by vigilant attention deficits during the PVT. These findings support the key role of vigilant attention in maintaining overall neurobehavioral function after sleep loss.Keywords: total sleep deprivation, partial sleep restriction, vigilant attention, inhibition control